Areas for benchmarking among SMEs - Syarizal Abdul Rahim; Norailis Ab. Wahab (2013)
Job creation, economic growth and innovation are partial of the achievement for SMEson the well-being of the economy for a particular country and society. Due to the reasons, there are lots of benchmarking activities conducted by government and private bodies through events that promote exposures for the SMEs in enhancing its capabilities. Thus, this paper aims to identify the areas within benchmarking activities that are implemented by local SMEs. Semi-structured interviews were conducted among 35 SMEs that were willing to participate voluntarily. This study found that management is the best driver of benchmarking adoption. Possibly, the closeness of relationship between management, suppliers and customers enhances support for benchmarking in the enterprises. It also revealed that SMEs benchmarked in only one specific area or in all aspects such as production (32.6%), operations management (17.0%), marketing (16.0%), information and communication technology (ICT) application (16.8%), financial (10.0%), and management (7.0%). Although the results should be taken with caution, nevertheless benchmarking is vital in facing new challenges and opportunities for success in productivity and profitability.